BIBLIOMETRIC ANALYSIS OF MATHEMATICAL COMMUNICATION SKILLS USING SCOPUS DATABASE - Yani, Nur Fitri; Soebagyo, Joko (Jurnal Pendidikan Matematika dan IPA, 2023)
The purpose of this study is to analyze how the development of research publication trends in mathematical communication skills in mathematics learning for the 2016-2021 period published in Scopus indexed scientific journals, review citation analysis, and examine trend analysis of terms or keywords by authors in journals and journals. The sample uses 142 article titles. Bibliometric analysis methods through quantitative studies are used to collect, process, and analyze data related to mathematical communication skills in mathematics learning. Data retrieval using PoP (Publish or Perish) software. Data analysis is descriptive quantitative. The results showed that the trend of scientific publications regarding the trend of mathematical communication skills increased from 2016-2021. It can be seen from the data that the number of articles published during 2019-2020 was the most researched on mathematical communication skills. The most cited articles related to mathematical communication skills occurred in 2019 with 97 citations. The Pisa question, communication technology, prospective mathematics teacher and self-efficacy are variables that are still rarely studied.